2018
DOI: 10.1186/s12944-018-0796-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective plasma lipid profiling in individuals with and without depression

Abstract: BackgroundSo far, studies on possible association of plasma lipid levels and depressive disorder are contradictory. This prospective work aimed at assessing a plasma lipid profile in individuals with major depression and healthy controls.MethodsIn total, 94 patients with major depression and 152 healthy controls were included in this prospective study. After an overnight fasting state of 12 h they underwent blood drawing for triglyzerides (TG), total cholesterol, low-density lipoprotein (LDL)- and high-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 26 publications
4
34
4
Order By: Relevance
“…Some studies reported raised TG in depression(e.g. [42][43][44][45] ), but meta-analysis on the topic is lacking. Of note, a prospective study in Finnish young adults showed that steeply rising TG levels throughout childhood and adulthood was associated with increased DS in adulthood 43 , consistent with the present finding of a causal role of TG in the development of DS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported raised TG in depression(e.g. [42][43][44][45] ), but meta-analysis on the topic is lacking. Of note, a prospective study in Finnish young adults showed that steeply rising TG levels throughout childhood and adulthood was associated with increased DS in adulthood 43 , consistent with the present finding of a causal role of TG in the development of DS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a relationship between low levels [ 13 ], others with high levels [ 14 ] of total cholesterol and depression [ 15 ]. Conflicting results are also related to the association of LDL- and HDL-cholesterol with depression.…”
Section: Introductionmentioning
confidence: 99%
“…HAMD-17 was developed by Max Hamilton in 1960 to assess the severity of depressive symptoms (51). BDI-II is a widely used assessment method to measure the presence and severity of depression-related symptoms (52). Therefore, we used HAMD-17 and BDI-II as the primary outcome indicators for assessing the degree and changes of depression in patients.…”
Section: Discussionmentioning
confidence: 99%